Proteasome inhibitors in cancer therapy: Treatment regimen and peripheral neuropathy as a side effect - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2017)
Proteasomal system plays an important role in protein turnover, which is essential for homeostasis of cells. Besides degradation of oxidized proteins, it is involved in the regulation of many different signaling pathways. These pathways include mainly cell differentiation, proliferation, apoptosis, transcriptional activation and angiogenesis. Thus, proteasomal system is a crucial target for treatment of several diseases including neurodegenerative diseases, cystic fibrosis, atherosclerosis, autoimmune diseases, diabetes and cancer. Over the last fifteen years, proteasome inhibitors have been tested to highlight their mechanisms of action and used in the clinic to treat different types of cancer. Proteasome inhibitors are mainly used in combinational therapy along with classical chemo-radiotherapy. Several studies have proved their significant effects but serious side effects such as peripheral neuropathy, limits their use in required effective doses. Recent studies focus on peripheral neuropathy as the primary side effect of proteasome inhibitors. Therefore, it is important to delineate the underlying mechanisms of peripheral neuropathy and develop new inhibitors according to obtained data. This review will detail the role of proteasome inhibition in cancer therapy and development of peripheral neuropathy as a side effect. Additionally, new approaches to prevent treatment limiting side effects will be discussed in order to help researchers in developing effective strategies to overcome side effects of proteasome inhibitors.
Keywords: Proteasome; Bortezomib; Carfilzomib; Chemotherapy; Neuropathy; NF-KAPPA-B; UBIQUITIN-INDEPENDENT DEGRADATION; VIVO SYNERGISTIC CYTOTOXICITY; DIAGNOSED MULTIPLE-MYELOMA; BORTEZOMIB PLUS MELPHALAN; IN-VIVO; INDUCED APOPTOSIS; BETA-CATENIN; RETINOBLASTOMA PROTEIN; SINGLE-AGENT